Survival Analysis of Breast Cancer Patients According to Intermediate and Endpoint Events: Applying Illness-Death Model - M Raesizadeh; M Seghatoleslami; M Hoseinzade; A Saki Malehi (مجله اپیدمیولوژی ایران, 2018)
Background and Objectives: Breast cancer is the leading cause of death from cancer among women. In developing countries, the patients’ survival is less than developed countries. Metastasis, as an intermediate event, affects the survival of breast cancer patients. This study aimed to evaluate the survival of patients after surgery considering metastasis, as the intermediate event, using the illness-death model. Methods: In this study, 165 cases of Iranian breast cancer patients who underwent surgery during 2006-2014 were investigated. The patients’ characteristics and their intermediate and final status were collected from their medical records. The illness-death model was used to assess prognostic factors in all stages of disease. Results: The risk of metastasis in patients with tumor size between 2-5 cm was 3.8 times higher than patients whose tumors were below 2 cm (P=0.009). Patients who had 3 to 6 lymph nodes involved were 3.1 times more likely to have metastases that those with less than 2 lymph nodes (P=0.003). Also, the grade of tumor and HER-2 had a significant role in metastasis (P=0.04). Conclusion: Using the illness-death model that is suitable for the analysis of such data, it was found that lymph node involved and tumor size had a significant role in metastasis. So, early detection of cancer is required to prevent metastasis and death.